A Golden2-like transcription factor, BnGLK1a, improves chloroplast development, photosynthesis, and seed weight in rapeseed - Qianwei Zhang; Yuanyi Mao; Zikun Zhao; Xin Hu; Ran Hu; Nengwen Yin; Xue Sun; Fujun Sun; Si Chen; Yuxiang Jiang; Liezhao Liu; Kun Lu; et al. (Journal of Integrative Agriculture)
Enhancing photosynthetic efficiency is a major goal for improving crop yields under agricultural field conditions and is associated with chloroplast biosynthesis and development. In this study, we demonstrate that Golden2-like 1a (BnGLK1a) plays an important role in regulating chloroplast development and photosynthetic efficiency. Overexpressing BnGLK1a resulted in significant increases in chlorophyll content, the number of thylakoid membrane layers and photosynthetic efficiency in Brassica napus, while knocking down BnGLK1a transcript levels through RNA interference (RNAi) had the opposite effects. A yeast two-hybrid screen revealed that BnGLK1a interacts with the abscisic acid receptor PYRABACTIN RESISTANCE 1-LIKE 1–2 (BnPYL1–2) and CONSTITUTIVE PHOTOMORPHOGENIC 9 SIGNALOSOME 5A subunit (BnCSN5A), which play essential roles in regulating chloroplast development and photosynthesis. Consistent with this, BnGLK1a-RNAi lines of B. napus display hypersensitivity to the abscisic acid (ABA) response. Importantly, overexpression of BnGLK1a resulted in a 10% increase in thousand-seed weight, whereas seeds from BnGLK1a-RNAi lines were 16% lighter than wild type. We propose that BnGLK1a could be a potential target in breeding for improving rapeseed productivity. Our results not only provide insights into the mechanisms of BnGLK1a function, but also offer a potential approach for improving the productivity of Brassica species.